GOVERNANCE CHALLENGES AND FAILURE OF PROJECT IMPLEMENTATION IN NIGERIA: A STUDY OF BENIN ELECTRICITY DISTRIBUTION COMPANY (BEDC) (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2023)
This study examined the challenges of governance and failure of projects implementation in the power sector under the control of BEDC in the four states under its jurisdiction or control. A cross-sectional research design and purposive sampling technique were adopted.  Questionnaire was employed as the research instrument for this study with 93 respondents deemed usable. Data collected were analysed using percentages and Pearson’s coefficient of correlation with the aid of Statistical Package for Social Sciences (SPSS) Version 22. T The study found that the Benin Electricity Distribution Company (BEDC) is responsible for failure in projects implementation as per the reasons received from the responses which are; there is no corporate accountability and transparency in the company, poor leadership and a continued work ethics violation by the management cadre of the company, this off course will always impact on project implementation negatively. Inaccurate project costing, poor planning and estimation also leads to failure in project implementation. The study also discovered that poor/bad governance was the root cause of project execution failure. It was discovered that the government's insufficient funding for power projects makes implementations nearly impossible and contributes to ineffective electricity production, distribution, and supply. The study concluded that there is a significant relationship between poor/bad governance, the BEDC and failure in project implementation in the power sector. Conclusively, it will be simplified to say that the causes for failure in projects implementation in the power sector under the control of the Benin Electricity Distribution Company (BEDC) is been shared by the government and the BEDC. On the basis of these findings of this study, the author recommends among others that the government should team up with the electricity distribution companies to provide pre-paid meters to all electricity end users. The unavailability of prepaid meters leads to overbilling of customers; and at this, people are discouraged to make full payments. But with the provision of prepaid meters, end users will pay according to consumption, which therefore means that individuals cannot have access to electricity when they fail to subscribe.